EVIDENCE-BASED PREVENTION OF TUBOTITIS: CURRENT TRENDS AND PRACTICES - Khondamir A. Jurayev; Sanjar B. Usmonov (Modern American Journals, 2025)
Tubotitis, or Eustachian tube inflammation, is a condition characterized by dysfunction in the air passage connecting the nasopharynx and the middle ear. This article explores the etiological factors contributing to the development of tubotitis and presents evidence-based preventive strategies aimed at mitigating its occurrence. Special attention is given to modifiable risk factors, such as upper respiratory tract infections and poor hygiene practices. The significance of early diagnosis, lifestyle modification, immune strengthening, and personal hygiene in preventing tubotitis is emphasized. The review aims to enhance awareness among healthcare professionals and the general public regarding the importance of timely and integrated preventive approaches.
Keywords: Tubotitis, Eustachian tube inflammation, hearing impairment, prophylaxis, nasopharyngeal infections, acute respiratory viral infections (ARVI), hygiene, immunity, prevention strategies.